2014
DOI: 10.7763/ijssh.2014.v4.404
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Distributive Justice, Procedural Justice, and Affective Commitment on Turnover Intention among Public and Private Sector Employees in Malaysia

Abstract: Abstract-This paper examined the impact of distributive and procedural justice on turnover intention via affective commitment. Specifically, it is predicted that when the distributive and procedural justice relating to compensation are perceived to be fair, employees are more affectively committed to the organization and expressed lower turnover intention. A total of 226 respondents throughout Malaysia participated in this study. Partial least squares of structural equation modeling was used in the study. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
(57 reference statements)
2
15
0
Order By: Relevance
“…Thirdly, a negative relationship is found between distributive justice and turnover intention in this study. These findings are by previous studies from Poon (2012) and Gim and Desa (2014) who state that if employees believe that fairness exists in the outcomes of rewards, they will prefer to stay in their organizations. All these study results show that distributive justice and POS influences employees' intention to leave.…”
Section: Summary Of the Findingssupporting
confidence: 70%
See 1 more Smart Citation
“…Thirdly, a negative relationship is found between distributive justice and turnover intention in this study. These findings are by previous studies from Poon (2012) and Gim and Desa (2014) who state that if employees believe that fairness exists in the outcomes of rewards, they will prefer to stay in their organizations. All these study results show that distributive justice and POS influences employees' intention to leave.…”
Section: Summary Of the Findingssupporting
confidence: 70%
“…The research concluded that one of the primary factors for turnover intention is organizational justice, namely distributive justice and procedural justice (Loi, Hang-yue, & Foley, 2006;Gim & Desa, 2014). Distributive justice is the fairness perception of outcomes designated while procedural justice is the fairness perception of the procedure utilized in resulting in the allocated outcomes (Folger & Cropanzano, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The term OJ is closely related to the concept of fairness in the workplace [24]. [25] pointed out that researchers have operationalized the OJ into two dimensions (distributive justice and procedural justice) and other to three dimensions (DJ, PJ, and IJ) or four dimensions by adding the informational justice.…”
Section: B Organizational Justicementioning
confidence: 99%
“…But in real sense, the usefulness of personality in relation to such anticipated behaviours has been observed in the trait of conscientiousness to be very limited (Shein, 1996). Quite a good number of studies have been done concerning social exchange relation on how employees' engage in beneficial behaviour in order to receive good attention from their organization (Beck & Wilson, 2000;Gim & Desa, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…According to Gim and Desa (2014) the belief that culture energizes employees' behaviour has not adequately been substantiated by empirical review. Hence, this leads to the current debate on the influences of culture on employees' behaviour.…”
Section: Introductionmentioning
confidence: 99%